1995
DOI: 10.1037/1064-1297.3.3.232
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dopamine reuptake inhibitors on food- and cocaine-maintained responding: II. Comparisons with other drugs and repeated administrations.

Abstract: A previous study (J.R. Glowa, F.H.E. showed that acute doses of GBR 12909 selectively decreased cocaine-maintained responding without affecting foodmaintained responding. This report extended these observations to some related drugs and to the effects of repeated administration. When responding was maintained under a multiple fixed ratio (FR) 30 food, FR 30 cocaine schedule, acute doses of GBR 12935, CFT, and d-amphetamine decreased cocaine-maintained responding more than food-maintained responding. However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
70
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(75 citation statements)
references
References 12 publications
5
70
0
Order By: Relevance
“…Such procedures are used to evaluate candidate medications for the treatment of dependence on cocaine or other drugs. Results indicate that GBR 12909 decreased rates of responding maintained by cocaine without affecting rates of responding maintained by food, suggesting antagonism of cocaine's reinforcing effects at doses that might not be hampered by side-effects (e.g., Glowa et al 1995). Of interest, other indirect dopamine agonists (e.g.…”
Section: Experimental Findingsmentioning
confidence: 90%
“…Such procedures are used to evaluate candidate medications for the treatment of dependence on cocaine or other drugs. Results indicate that GBR 12909 decreased rates of responding maintained by cocaine without affecting rates of responding maintained by food, suggesting antagonism of cocaine's reinforcing effects at doses that might not be hampered by side-effects (e.g., Glowa et al 1995). Of interest, other indirect dopamine agonists (e.g.…”
Section: Experimental Findingsmentioning
confidence: 90%
“…Animal studies have shown that pretreatment with the dopamine uptake inhibitor, GBR 12909 (Glowa et al 1995a(Glowa et al , 1995bTella 1995), and other potent dopamine uptake inhibitors (Mansbach et al 1993;Dworkin et al 1998) decreased cocaine selfadministration. Effects of the non-selective monoamine uptake inhibitor, indatraline, have also been examined.…”
Section: Introductionmentioning
confidence: 98%
“…Selective dopamine reuptake inhibitors have been extensively evaluated in drug self-administration procedures in non-human primates (Bergman et al 1989;Kleven and Woolverton 1993;Mansbach and Balster 1993;Glowa et al 1995;Nader et al 1997;Negus et al 1999), and rapid assessment procedures have been utilized for this objective (Skjoldager et al 1993). Dopaminergic agents are particularly interesting because, although cocaine non-selectively blocks the reuptake of dopamine, norepinephrine, and serotonin (Blackburn et al 1967;Coyle and Snyder 1969;Harris and Baldessarini 1973), the abuse-related effects of cocaine have been most compellingly related to its action as an indirect dopamine agonist (Johanson and Fischman 1989;Koob et al 1997;Caine 1998aCaine , 1998b.…”
Section: Introductionmentioning
confidence: 99%